PENERAPAN MODEL DELONE & MCLEAN UNTUK MENGUKUR KEBERHASILAN LAYANAN PENGADUAN APLIKASI PLN MOBILE PADA PT.PLN (PERSERO) CABANG LUWUK - Junaptha Adrianto Subito; Nina Fapari Arif; Andi Harmoko Arifin (Politeknik Negeri Ambon, 2026)
Introduction: This study measures the success rate of customer complaint services using the PLN Mobile application at PT. PLN (Persero) Luwuk Branch Office by applying the Delone and McLean (2003) model. The model examines the influence of System Quality, Information Quality, Service Quality, and Ease of Use on User Intention and Satisfaction, and their contributions to net benefits.Methods: A quantitative explanatory approach was used, based on a survey of 120 respondents who used the complaint feature. Data analysis was performed using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach in SmartPLS.Results: Of the eleven hypotheses tested, five were significant: System Quality had a positive effect on both User Intention and User Satisfaction; Ease of Use had a positive effect on User Satisfaction; and both User Intention and User Satisfaction had a positive effect on Net Benefit. On the other hand, six relationships were not significant: the influence of Service Quality and Information Quality on Intention to Use and User Satisfaction, as well as the effect of Ease of Use on User Intention and user satisfaction. This research contributes practical implications for improving applications and enriching theories regarding the adaptation of information system success models in the realm of digital public services. Keywords: Complaint Service, Delone and McLean’s Model, Information System Success, PLN Mobile, User Satisfaction